2021
DOI: 10.3390/rs13224595
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Seasonal and Diurnal Cycles of TOA Shortwave Radiations from DSCOVR/EPIC, CERES, MERRA-2, and ERA5

Abstract: Reflected shortwave (SW) solar radiations at the top of atmosphere from Clouds and the Earth’s Radiant Energy System (CERES), Modern Era-Retrospective analysis for Research and Applications version 2 (MERRA-2), and ECMWF Reanalysis 5th Generation (ERA5) are examined to better understand their differences in spatial and temporal variations (seasonal and diurnal cycle timescale) with respect to the observations from the Earth Polychromatic Imaging Camera (EPIC) on the Deep Space Climate Observatory (DSCOVR) sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, if the diurnal variation is not symmetric with respect to noon, their average would not cancel the SH-NH differences. A recent study showed that the SW diurnal variation from the CERES EBAF is somewhat different from the one inferred from the DSCOVR/EPIC observation (Lim et al, 2021). In addition, the rate of daytime cloud fraction changes from DSCOVR/EPIC observations is not symmetric about noon either (Delgado-Bonal et al, 2021).…”
Section: Hemispheric Asymmetry In Sw Fluxmentioning
confidence: 88%
“…However, if the diurnal variation is not symmetric with respect to noon, their average would not cancel the SH-NH differences. A recent study showed that the SW diurnal variation from the CERES EBAF is somewhat different from the one inferred from the DSCOVR/EPIC observation (Lim et al, 2021). In addition, the rate of daytime cloud fraction changes from DSCOVR/EPIC observations is not symmetric about noon either (Delgado-Bonal et al, 2021).…”
Section: Hemispheric Asymmetry In Sw Fluxmentioning
confidence: 88%